The secret life of Walter Kitty - Santat, Dan 1975- (Alfred A. Knopf, 2007)
Walter, an ordinary housecat, fantasizes about the daring adventures of his alter ego, Fang
Keywords: Cats / Juvenile fiction; Picture books for children; Cats / Fiction; Humorous stories; Cats; Humorous fiction; Fiction; Juvenile works; Picture books; Children's picture books; Children's fiction; Bilderbuch